2020
DOI: 10.35860/iarej.686459
|View full text |Cite
|
Sign up to set email alerts
|

Taguchi method for investigation of the effect of TBC coatings on NiCr bond-coated diesel engine on exhaust gas emissions

Abstract: The NiCr bond coated piston and valve surfaces were coated with Cr2O3, Cr2O3 + 50% Al2O3, Cr2O3 + 75% Al2O3 powders by thermal barrier coating (TBC). The influence of the coating layers on CO, CO2, HC and NOx was examined both statistically and experimentally. The statistical investigation was carried out by using Taguchi analysis. According to the experimental test results obtained at different engine speeds, the sample with the highest CO2 value was found at 2600 rpm in the Cr2O3 + 75% Al2O3 coated diesel en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Authors are serkan Ozel, Erdinc Viral, Murat Binici. [16] published title paper" Taguchi method for investigation of the effect of TBC coating on NiCr bond-coated diesel engine on exhaust gas emissions" in this journal International advance researches and engineering journal. They have found this type of result while carbon monoxide(CO) and hydrocarbon (HC) emission are lower in cr2o3 ,cr2o3+50% Al2o3 and cr2o3 + 85% Al2o3 ceramic coated diesel engines compared to standard diesel engine.…”
Section: Limitations Of Plasma Processmentioning
confidence: 99%
“…Authors are serkan Ozel, Erdinc Viral, Murat Binici. [16] published title paper" Taguchi method for investigation of the effect of TBC coating on NiCr bond-coated diesel engine on exhaust gas emissions" in this journal International advance researches and engineering journal. They have found this type of result while carbon monoxide(CO) and hydrocarbon (HC) emission are lower in cr2o3 ,cr2o3+50% Al2o3 and cr2o3 + 85% Al2o3 ceramic coated diesel engines compared to standard diesel engine.…”
Section: Limitations Of Plasma Processmentioning
confidence: 99%
“…This is the desired result because it is concluded that there is a thermal barrier coating inside the cylinder with the ceramic coating. Since the thermal conductivity coefficients of Cr2O3 and Al2O3 materials are lower than the standard combustion chamber of the engine (AlSi), it traps the temperatures in the cylinder, there by increasing the end of combustion temperatures inside the cylinder [22][23][24][25][26]. coated engine and 12.73% in Cr2O3+75%Al2O3 coated engine.…”
Section: Engine Performance Of Coated Enginementioning
confidence: 99%
“…Genicci Taguchi developed a statistical method [19][20][21][22] to determine the relationship between the parameters that affect the process and the results by making a few experiments, observations, or analyzes as possible. This method is used in many different fields [23][24][25][26][27]. The basic methodology of the Taguchi method consists of four steps: (1) determining the parameters and their levels that affect the process, (2) choosing an appropriate orthogonal index table, (3) performing the experiments and analyzing the results, and (4) obtaining and verifying the optimum results.…”
Section: Introductionmentioning
confidence: 99%